Spectroscopic and Theoretical Studies of Hg(II) Complexation with Some Dicysteinyl Tetrapeptides - Elliot Springfield; Alana Willis; John Merle; Johanna Mazlo; Maria Ngu-Schwemlein (Bioinorganic Chemistry and Applications)
Tetrapeptides containing a Cys-Gly-Cys motif and a propensity to adopt a reverse-turn structure were synthesized to evaluate how O-, N-, H-, and aromatic π donor groups might contribute to mercury(II) complex formation. Tetrapeptides Xaa-Cys-Gly-Cys, where Xaa is glycine, glutamate, histidine, or tryptophan, were prepared and reacted with mercury(II) chloride. Their complexation with mercury(II) was studied by spectroscopic methods and computational modeling. UV-vis studies confirmed that mercury(II) binds to the cysteinyl thiolates as indicated by characteristic ligand-to-metal-charge-transfer transitions for bisthiolated S-Hg-S complexes, which correspond to 1 : 1 mercury-peptide complex formation. ESI-MS data also showed dominant 1 : 1 mercury-peptide adducts that are consistent with double deprotonations from the cysteinyl thiols to form thiolates. These complexes exhibited a strong positive circular dichroism band at 210 nm and a negative band at 193 nm, indicating that these peptides adopted a β-turn structure after binding mercury(II). Theoretical studies confirmed that optimized 1 : 1 mercury-peptide complexes adopt β-turns stabilized by intramolecular hydrogen bonds. These optimized structures also illustrate how specific N-terminal side-chain donor groups can assume intramolecular interactions and contribute to complex stability. Fluorescence quenching results provided supporting data that the indole donor group could interact with the coordinated mercury. The results from this study indicate that N-terminal side-chain residues containing carboxylate, imidazole, or indole groups can participate in stabilizing dithiolated mercury(II) complexes. These structural insights on peripheral mercury-peptide interactions provide additional understanding of the chemistry of mercury(II) with side-chain donor groups in peptides.